Collagen nanofiber containing silver nanoparticles for improved wound-healing applications. (2nd July 2016) - Rath, Goutam; Hussain, Taqadus; Chauhan, Gaurav; Garg, Tarun; Goyal, Amit Kumar
Abstract: Electrospun nanofibers showing great promise for fabricating nanostructured materials might help to improve the quality of wound care. The present study aimed to investigate the wound-healing potential of collagen nanofiber mats containing silver nanoparticles. Silver nanoparticles (AgNPs) synthesized by the chemical reduction method were incorporated in collagen nanofibers during the electrospinning process. Characterization of electrospun nanofiber mats revealed a mean fiber diameters in the range of 300–700 nm with a sustained release of silver ions shown to follow pseudo-order kinetics. MIC of AgNPs against Staphylococcus aureus and Pseudomonas aeruginosa were evaluated using micro-dilution assay and further antimicrobial activity of fabricated nanofibers was performed. Finally, in vivo studies were performed to demonstrate the wound-healing efficacy of composite nanofibers. In vitro results confirmed the potential antimicrobial efficacy provided by AgNPs and AgNPs composite nanofibers, essential to provide an aseptic environment at the wound site. In vivo study revealed that the rate of wound healing of the composite nanofiber mats was found to be accelerated compared with plain collagen nanofibers. Histology analysis revealed an accelerated re-epithelization, collagen production, and better wound contraction with AgNPs composite collagen nanofibers.